Minimising the environmental footprint of industrial-scaled cleaning processes by optimisation of a novel clean-in-place system protocol - Palabiyik, Ibrahim; Yilmaz, Mustafa Tahsin; Fryer, Peter J.; Robbins, Phillip T.; Toker, Omer Said (ELSEVIER SCI LTD, 2015)
Cleaning of food fouling deposits in processing equipment is costly and time consuming. Fouling deposits form as a result of adhesion of species to the surface and cohesion between elements of the material. Cleaning can result from either or both adhesive and cohesive failure. In this study, the aim was to investigate the removal kinetics of an adhesive material and to design a novel cleaning in place (CIP) protocol for these kinds of materials at industrial scale to reduce environmental impact of cleaning processes. It was detected that different variables controlled the cleaning process in removal of adhesive deposit Temperature was not found as a significant variable in the initial stage of cleaning. Velocity of cleaning water controlled the cleaning at this stage when top layers of the deposit were removed by fluid mechanical removal due to breakdown of weak cohesive interaction. In the later cleaning stage, both velocity and temperature significantly contributed to cleaning, which suggested that both hydrodynamic forces and rheological changes are needed to overcome adhesion forces between the deposit and surface. Hence, a novel two step CIP protocol was proposed due to existence of different mechanisms in cleaning. When compared with conventional one step CIP protocols currently used in the processing plants, the proposed CIP protocol reduced the energy consumption by 40% without decreasing the cleaning efficiency. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Cleaning in place; Optimisation; Adhesive material; Pilot scale experiments; Response surface methodology; RESPONSE-SURFACE METHODOLOGY; DEPOSITS; MICROMANIPULATION; WATER; WHEY; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology